DEVELOPMENT OF SNAKE AND LADDER GAME MEDIA TO ENHANCE THE CAREER EXPLORATION OF JUNIOR HIGH SCHOOL STUDENTS - Adilah Muthiah Khansa; Rita Eka Izzaty (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper contends that the contextual worship debate ought to go beyond issues of style adjustment and aesthetic appropriateness to a more stringent practical-theological description of how worship conveys faith, shapes ecclesial identity and is not subject to instrumental diminution. With an interpretive library research design, the article peruses the theory of communicative action by Jurgen Habermas and some of the most significant discussions in practical theology, liturgical studies, digital ecclesiology, and Indonesian contextual theology. It is revealed that the best way to understand worship is as communicative-theological praxis where the truth claims, normative claims, and expressive claims are united in the lifeworld of the church. In that regard, cultural proximity, technological sophistication, or numerical appeal cannot be considered as a judgment of contextualization. It has to be assessed on whether it maintains theological fidelity, enhances communicative intelligibility, nurtures participatory reciprocity and fosters ethical-transformative fruit in community life. One of the new aspects of the article is the suggestion of these four criteria as an evaluation tool to differentiate between contextualization and instrumentalization. The existence of such a framework enables the evaluation of digital, hybrid, and culture-based worship practices without either reduction to nostalgic traditionalism or market-driven innovationism. The conclusion of the study is that practical theology is a critical and constructive exercise: it assists churches to make the gospel relevant to them in specific cultural ways and to protect worship against being turned into a spectacle or a product, an efficient religious service.